2020
DOI: 10.1038/s41598-020-77293-7
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative transcriptome analysis implied a ZEP paralog was a key gene involved in carotenoid accumulation in yellow-fleshed sweetpotato

Abstract: The mechanisms of carotenoid accumulation in yellow-fleshed sweetpotato cultivars are unclear. In this study, we compared the transcriptome profiles of a yellow-fleshed cultivar, Beniharuka (BH) and two of its spontaneous white-fleshed mutants (WH2 and WH3) to reveal the genes involved in yellow flesh. As a result of RNA sequencing, a total of 185 differentially expressed genes (DEGs) were commonly detected in WH2 and WH3 compared to BH. Of these genes, 85 DEGs and 100 DEGs were commonly upregulated and downre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…Our results showed that the three PSY genes have differentially expressed patterns during the panicle development stage, suggesting that they have differential functions in regulating carotenoid metabolism ux [49]. Additionally, many studies have demonstrated that ZEP is an important node for ne-tuning carotenoid metabolism in Arabidopsis [50,51]. The SNP variants of ZEP in sorghum and Arabidopsis were signi cantly correlated with the zeaxanthin content and lutein/zeaxanthin ratio [52,53].…”
Section: Characteristics Of Carotenoid Content Variations In Plantsmentioning
confidence: 60%
“…Our results showed that the three PSY genes have differentially expressed patterns during the panicle development stage, suggesting that they have differential functions in regulating carotenoid metabolism ux [49]. Additionally, many studies have demonstrated that ZEP is an important node for ne-tuning carotenoid metabolism in Arabidopsis [50,51]. The SNP variants of ZEP in sorghum and Arabidopsis were signi cantly correlated with the zeaxanthin content and lutein/zeaxanthin ratio [52,53].…”
Section: Characteristics Of Carotenoid Content Variations In Plantsmentioning
confidence: 60%
“…Studies have shown that CRTISO (prolycopene isomerase) is one of the enzymes that catalyze the synthesis of lycopene from phytoene, and has a critical role in carotenoid biosynthesis pathway in the dark and in nonphotosynthetic tissues (Isaacson et al, 2002). Suematsu et al (Suematsu et al, 2020) identified ZEP paralog (g1103.t1) as a key gene involves in carotenoid accumulation by regulating epoxidation of b-carotene and b-cryptoxanthin in yellowfleshed sweetpotato. Cytochrome P450 (CYP97) family is the key enzyme that catalyzes carotene to produce xanthophylls (Li and Wei 2020).…”
Section: The Key Genes Involved In Carotenoid Metabolic Pathwaymentioning
confidence: 99%
“…In the δ-carotene branch, lutein is finally produced by lycopene ϵ-cyclase ( LCYE ), lycopene β-cyclase ( LCYB ), and carotenoid ϵ-hydroxylase (CYP97C1) and β-carotene hydroxylase ( CHYB ). In the γ-carotene branch, the carotenoids synthesized with the help of lycopene β-cyclase ( LCYB ), β-carotene hydroxylase ( CHYB ), zeaxanthin epoxidase ( ZEP ), violaxanthin de-epoxidase ( VDE ) ( Liu et al., 2020 ; Suematsu et al., 2020 ; Xu et al., 2021 ; KEGG, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are no reports regarding the molecular mechanisms underlying weevil resistance in sweetpotato using transcriptome-based analysis. Recently, with the decreasing costs and increasing throughput of NGS technology, several groups have reported large-scale transcriptome studies in sweetpotato, revealing the key genes and a comprehensive knowledge of the mechanisms underlying important agricultural traits [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. In addition, the whole genome sequence and functionally annotated genes of the closely related diploid species Ipomoea trifida have been previously released [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%